Integritas Akademik Calon Dharmaduta (Studi pada STABN di Indonesia) - Ahsanul Khair Asdar (Jurnal Pelita Dharma, 2019)
This study was a descriptive study with quantitative approach which aimed to describe the academic integrity of Dharmaduta students on State Buddhist College in Indonesia. The respondents in this study were 37 college students from the Department of Dharmaduta which were selected using cluster random sampling from two state Buddhist Colleges in Indonesia. The data were collected using academic integrity questionnaire with five dimensions, namely honesty, trust, fairness, respect, and responsibility. The questionnaire consisted of 39 items with Likert modification scale (four options). The data were analyzed using descriptive statistics. The result of this study showed that the academic integrity of Dharmaduta department college students on state Buddhist colleges in Indonesia was in the high category. Meanwhile, if viewed according to gender, the academic integrity of male students of the Dharmaduta department at state Buddhist colleges in Indonesia was in the high category, the academic integrity of female students was also in the high category. If viewed according to the dimensions, the dimension which has the highest average score was fairness while the lowest average score was trust.Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif yang bertujuan untuk menggambarkan integritas akademik calon Dharmaduta yang sedang menempuh pendidikan pada Jurusan Dharmaduta STABN di Indonesia. Responden yang digunakan di dalam penelitian ini adalah 37 mahasiswa Jurusan Dharmaduta yang dipilih menggunakan cluster random sampling dari dua STABN di Indonesia. Data penelitian dikumpulkan menggunakan angket integritas akademik dengan dimensi kejujuran (honesty), kepercayaan (trust), keadilan (fairness), rasa hormat (respect), dan tanggung jawab (responsibility). Instrumen tersebut memuat 39 butir pernyataan yang setiap butir pernyataan menggunakan skala Likert termodifikasi (skala genap). Keseluruhan data dianalisis dengan menggunakan statistika deskriptif. Hasil penelitian menunjukkan bahwa integritas akademik mahasiswa Jurusan Dharmaduta pada STABN di Indonesia berada pada kategori tinggi. Sementara jika ditinjau menurut jenis kelamin, maka integritas akademik mahasiswa laki-laki Jurusan Dharmaduta pada STABN di Indonesia berada pada kategori tinggi, demikian halnya dengan integritas akademik mahasiswa perempuan yang juga berada pada kategori tinggi. Jika ditinjau menurut dimensi, yang memiliki rata-rata skor tertinggi adalah keadilan dan rata-rata skor terendah adalah kepercayaan.